Mobilisasi Dini di Intensive Care Unit (ICU): Tinjauan Pustaka - Dian Marta Sari; Siti Chandra Widjanantie; Dewi Poerwandari; Anitta Florence Stans Paulus; Deddy Tedjasukmana; Nury Nusdwinuringtyas; Anita Ratnawati; Hening Laswati Putra (Majalah Kedokteran Indonesia, 2022)
Patients in the intensive care unit (ICU) usually have muscle weakness problems that are not related to their primary diseases when admitted ICU. This problem may become a clinical syndrome that we called ICU-Acquired Weakness (ICU-AW). There is currently no specific treatment for ICU-AW, therefore preventing patients from ICU-AW by controlling associated risk factors such as immobility, becoming a critical approach. Early mobilization (EM) has many benefits in the ICU setting for patients with or without mechanical ventilation. Besides that, the realization of EM needs consider the safety criteria and the barriers to their application. Thus, there are guidelines for the realization of EM to give the best outcomes while minimalizing the adverse events.